PENGARUH DISIPLIN KERJA TERHADAP KINERJA GURU DI SMP N 23 PEKANBARU - Rahmat, Yogie (Sekolah Tinggi Ilmu Ekonomi Riau, 2019)
Abstract: This research was conducted at SMP N 23 Pekanbaru which is located at Jl. Garuda Sakti Km. 3 Simpang Baru Tampan, Pekanbaru. This study aims to determine the Effect of Work Discipline on Teacher Performance in Pekanbaru SMP N 23, the study sample was 54 respondents. Based on the results of the study it is known that there are influences of work discipline with the regression equation Y = 9.346+ 0.795X, based on the results of the T test, Calculate at 8.004> Ttable (2006) with sig. (0,000 <0,05). The meaning is that the independent variable (work discipline) has a significant effect on the dependent variable (Teacher Performance) in Pekanbaru N 23 Junior High School. Based on the results of the Coefficient of Determination test (R2) The magnitude of the influence of work discipline on the performance of teachers in Pekanbaru N 23 Middle School is 55.2% while the remaining 44.8% is influenced by other variables not included in this study.